Conceptual Framework for Evaluating Intuitive Interaction Based on Image Schemas. Issue 3 (20th January 2015) - Kess Asikhia, Obokhai; Setchi, Rossitza; Hicks, Yulia; Walters, Andrew
Abstract : Intuitive interaction is an important aspect of usability in interface design. This paper contributes to the research in this area by proposing a conceptual framework for evaluating intuitive interaction based on image schemas. The framework comprises four phases: goal identification, image schemas extraction, analysis and assessment. It quantifies intuitive interaction by comparing the image schemas envisaged by the designer of a product with those used by its users. The proposed framework is evaluated through a study involving 42 participants completing a set task with a product. The study identified the image schemas, which were correctly used in accordance with the designer's intent and those that were incorrectly used and contributed to the difficulties that many participants experienced. The inter-rater reliability and empirical validity were examined. The proposed framework provides a structured approach to usability testing by enabling both quantitative and qualitative evaluation of intuitive interaction.